Ascending Aortic Aneurysm and Dissection Secondary to Bicuspid Aortic Valve with Concomitant Coarctation of Descending Aorta Successfully Repaired with Extracorporeal Membrane Oxygenation Support: A Case Report - Qin Jiang; Juan Du; Tao Yu; Xiaobo Huang; Mingliang Zuo; Keli Huang; Tianyu Xu; Xiaoxia Fu (Cardiology Discovery)
Abstract. Type A aortic aneurysm and dissection secondary to bicuspid aortic valve (BAV) with untreated coarctation of the aorta (CoA) in adults is a rare finding because there are almost no “abnormalities” in these patients’ medical histories. Here, we report on a 47-year-old man with unexplained weakness followed by unconsciousness. He was diagnosed with cardiogenic shock and underwent venoarterial extracorporeal membrane oxygenation (VA-ECMO). BAV, ascending aortic aneurysm and dissection (based on bedside echocardiography) and concomitant CoA (based on computed tomography angiography) were confirmed. The patient then underwent emergency surgery including aortic root replacement with a composite mechanical valve conduit, additional ascending-to-descending aortic bypass, and coronary artery bypass grafting with a saphenous vein graft to the right coronary artery. After treatment, he recovered uneventfully. Thus, here we present a case involving a patient in a critical condition with ascending aortic aneurysm and dissection secondary to complex congenital heart defects, who was successfully treated with composite surgical procedures combined with life-saving VA-ECMO.